Dual-response hexagonal boron nitride in epoxy vitrimer nanocomposite for self-repairable and corrosion resistance coatings - Nurul Fatihah, Norapandi; Aiman Sofiah, Razlan; Chong, Kwok Feng; Nurjannah, Salim; Siti Maznah, Kabeb; Rasidi, Roslan; Nurul Huda, Abu Bakar (Malaysian Institute of Chemistry, 2026)
Epoxy vitrimers (EV) are known for their self-repairing properties, utilizing dynamic disulfide bonds that reformed under heat. However, their brittleness and softness limit practical use. Hexagonal boron nitride (hBN), with its high thermal conductivity and mechanical reinforcement, offers a solution. This study explores hBN at 0.5 wt.% and 1.0 wt.% in EV to assess self-repairing, mechanical integrity, and corrosion resistance. The 0.5 wt.% hBN formulation achieved rapid self-repairing in ~10 minutes, demonstrating hBN’s role in efficient heat transfer and bond reformation. The 1.0 wt.% formulation showed superior corrosion resistance and hydrophobicity due to hBN’s barrier properties. Knife-scratch tests revealed severe delamination in pure epoxy vitrimer, moderate in 1.0 wt.% hBN, and a clean cut in 0.5 wt.% hBN, indicating better mechanical integrity. Both loadings highlight hBN’s dual role in enhancing self-repairing and mechanical integrity. The study underscores the critical role of hBN dosage, as excess loading can compromise performance, offering insights for designing advanced self-repairing coatings.